PENGARUH KEADILAN PROSEDURAL TERIIADAP PERILAKU KEWARGAAN ORGANISASIONAL YANG DIMEDIASI DUKUNGAN ORGANISASIONAL PERSEPSIAN Studi di SMA Negeri 1 Slogohimo, Wonogiri - , Arsida Erma Avianti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of the study is to examine the effect of perceived procedural justice on organizational citizenship behavior mediated by perceived organizational support of high school teachers. The four hypotheses proposed are: (1) perceived procedural justice directly influences organizational citizenship behavior, (2) perceived procedural justice affects perceived organizational support, (3) perceived organizational support affects organizational citizenship behavior, (4 ) perceived procedural justice affects organizational citizenship behavior mediated by perceived organizational support. The subject of this study was teachers of SMAN 1 Slogohimo, Wonogiri. The method of data collection is survey using. The analytical tool used is hyrarchical regression analysis which is adopted from Baron and Kenny (1986). The results showed that there is a significant influence of the perceived procedural justice on organizational citizenship behavior directly as well as mediated by perceived organizational support. The mediation relationship was partial mediation which was marked by the decrease in the regression coefficient of a direct relationship.